Quadripartite Vision and Mission of Dog-Mediated Rabies Elimination: Cross Border Transmission Threats: Cross border transmission of dog-mediated rabies and the Quadripartite vision of 0 by 30 - Muhammad Hassnain; Waqas Ahmad; Qaiser Akram; Muhammad Akram Khan; Muhammad Amjad Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Dog-mediated rabies is an evident global health problem due to the transmission of bite injuries inflicted by free-roaming dogs in developing countries. More than 95% of human rabies cases are happening due to free-roaming dogs. The World Organization for Animal Health, World Health Organization, Global Alliance for the Control of Rabies, and the Food and Agriculture Organization of the United Nations jointly signed the agenda and mission to eliminate dog-mediated human rabies by the end of 2030. The vision has been set to combat this oldest recorded infectious disease of mankind, but it seeks serious commitment, planning, and investment in the developing countries of Asia and Africa where the legislative involvement and overhead support of their respective government are already deficient. Variable challenges to attain this vision in diverse countries exist, and one of the major issues is the crossborder transmission risks of circulating strains of rabies viruses through animal reservoirs and trades. The present review article has been designed to investigate the global purposes and motives of various activities and working groups of the quadripartite and the United Against Rabies (UAR) forum with a special focus on developing countries and the existing One Health approach. Moreover, various strains and risk factors of rabies virus at cross-regional borders have also been highlighted by searching articles through various online databases such as Google Scholar, PubMed, ScienceDirect, and Google. A well-designed surveillance system and support from the governments may foster this challenging mission of the quadripartite.